2013
DOI: 10.1098/rstb.2012.0321
|View full text |Cite
|
Sign up to set email alerts
|

Organic cofactors in the metabolism of Dehalococcoides mccartyi strains

Abstract: Dehalococcoides mccartyi strains are strictly anaerobic organisms specialized to grow with halogenated compounds as electron acceptor via a respiratory process. Their genomes are among the smallest known for free-living organisms, and the embedded gene set reflects their strong specialization. Here, we briefly review main characteristics of published Dehalococcoides genomes and show how genome information together with cultivation and biochemical experiments have contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 74 publications
0
45
0
Order By: Relevance
“…The [NiFe] hydrogenase Hup is the predominant hydrogenase predicted to be involved in the oxidation of hydrogen (5,15). At the protein and transcript levels, Hup subunits have often been detected at levels similar to those of DET0187 (a formate dehydrogenase-like protein) in multiple D. mccartyi strains (15,16,46). Both of these enzymes are potentially involved in electron transport processes, passing a low-potential electron to a Fe-S small protein (47).…”
Section: Genomic Differences Betweenmentioning
confidence: 99%
“…The [NiFe] hydrogenase Hup is the predominant hydrogenase predicted to be involved in the oxidation of hydrogen (5,15). At the protein and transcript levels, Hup subunits have often been detected at levels similar to those of DET0187 (a formate dehydrogenase-like protein) in multiple D. mccartyi strains (15,16,46). Both of these enzymes are potentially involved in electron transport processes, passing a low-potential electron to a Fe-S small protein (47).…”
Section: Genomic Differences Betweenmentioning
confidence: 99%
“…However, the mechanisms that regulate the activity of D. mccartyi within natural ecosystems and shape its functional robustness in disturbed environments are poorly understood due to multiscale microbial community complexity and heterogeneity of biogeochemical processes involved in the sequential degradation (3,4). D. mccartyi exhibits specific restrictive metabolic requirements for a variety of exogenous compounds, such as hydrogen, acetate, corrinoids, biotin, and thiamine, which can be supplied by other microbial genera through a complex metabolic network (1,(5)(6)(7)(8). Therefore, the growth of D. mccartyi is more robust within functionally diverse microbial communities that are deterministically assembled than in pure cultures (5,8,9).…”
mentioning
confidence: 99%
“…D. mccartyi exhibits specific restrictive metabolic requirements for a variety of exogenous compounds, such as hydrogen, acetate, corrinoids, biotin, and thiamine, which can be supplied by other microbial genera through a complex metabolic network (1,(5)(6)(7)(8). Therefore, the growth of D. mccartyi is more robust within functionally diverse microbial communities that are deterministically assembled than in pure cultures (5,8,9). Previous studies have shown that D. mccartyi uses hydrogen as its sole electron donor for TCE dechlorination and outcompetes other terminal electron-accepting processes such as methanogenesis and acetogenesis at low hydrogen partial pressures (10,11).…”
mentioning
confidence: 99%
“…Genomic analyses of sequenced D. mccartyi strains reveal a lack of complete corrinoid biosynthesis pathways, rendering D. mccartyi incapable of synthesizing corrinoids de novo (6,7). Exogenous cobalamin (a specific corrinoid also known as vitamin B 12 ) is generally added to grow D. mccartyi in isolation (8).…”
mentioning
confidence: 99%